1990
DOI: 10.1159/000181434
|View full text |Cite
|
Sign up to set email alerts
|

A Placebo-Controlled Trial of Intranasal Growth Hormone-Releasing Hormone [GHRH(l-44)-NH<sub>2</sub>] Administration in Normal Young Adults

Abstract: Growth hormone-releasing hormone, GHRH(l-44), was administered intranasally to 16 healthy young adult male volunteers in a placebo-controlled study using a dose of 1,000 µg dissolved in two different solvent vehicles: water alone and water with the surface tension-lowering agent Tween 80 (0.12%). The growth hormone (GH)-releasing effects of intranasal GHRH as well as that of the vehicle were established and compared to the effects of 80 µg intravenous GHRH. Plasma GH response was assessed by frequent blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…GRF has been shown to be effective in treating children with GH deficiency because of a hypothalamic disorder [3,4], However, the smallest analogues of GRF having full intrinsic biological activity still require the first 29 amino acids of the N terminus [5], GRF is orally inactive but is effective when given intranasally in addition to intravenous and subcutaneous administrations [6,7], GHRP-6 is a synthetic hexapeptide derived from en kephalin through computer modelling techniques [8,9], It stimulates the release of GH from pituitary cells via a unique mechanism which is different from that of GRF [10][11][12], Our data indicate that protein kinase C appears to play a major role in mediating the effect of GHRP-6 [12]. In addition to its in vitro effect, GHRP-6 also stimu lated GH secretion when given intravenously in a number of species including humans [9.…”
Section: Introductionmentioning
confidence: 99%
“…GRF has been shown to be effective in treating children with GH deficiency because of a hypothalamic disorder [3,4], However, the smallest analogues of GRF having full intrinsic biological activity still require the first 29 amino acids of the N terminus [5], GRF is orally inactive but is effective when given intranasally in addition to intravenous and subcutaneous administrations [6,7], GHRP-6 is a synthetic hexapeptide derived from en kephalin through computer modelling techniques [8,9], It stimulates the release of GH from pituitary cells via a unique mechanism which is different from that of GRF [10][11][12], Our data indicate that protein kinase C appears to play a major role in mediating the effect of GHRP-6 [12]. In addition to its in vitro effect, GHRP-6 also stimu lated GH secretion when given intravenously in a number of species including humans [9.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that GHRH, which in earlier trials did not show any serious side-effects (6,7), could be used as a therapeutic agent in children with hypothalamic GHD. A I-month trial in normal young adults has not shown a decline in plasma levels of GHRH and GH after intranasal administration of GHRH (8). Intranasal administration of GHRH to promote growth could thus be an attractive alternative to daily injections of GH.…”
mentioning
confidence: 99%